A new class of self-healable hydrophobic materials based on ABA triblock copolymer via RAFT polymerization and Diels-Alder "click chemistry". (16th June 2017) - Pramanik, Nabendu B.; Mondal, Prantik; Mukherjee, Rabibrata; Singha, Nikhil K.
Abstract: This investigation reports the preparation of a new self-healing ABA tri-block copolymer (BCP) poly(furfuryl methacrylate- b -poly(dimethyl siloxane)- b -poly(furfuryl methacrylate) (PFMA- b -PDMS- b -PFMA) (FDF) via RAFT polymerization using PDMS-CTA as macro-RAFT agent. The formation of FDF triblock copolymer was confirmed by 1 H NMR, GPC and DSC analyses. The phase segregated domain morphology of the synthesized BCP films as a function of PFMA fraction was studied via an AFM. In this BCP, Diels-Alder (DA) click reaction was carried out between the reactive furfuryl group in PFMA unit as diene with different maleimides as dienophile. While the presence of the PFMA unit makes the triblock copolymer thermally amendable and the PDMS present in the matrix makes the BCP ideally suited for hydrophobic self-healing applications. The hydrophobic nature of the triblock copolymer was studied by water contact angle (WCA) measurement and the self-healing property was studied by DSC and SEM analyses. Graphical abstract: A new self-healable hydrophobic polymeric material based on poly(furfuryl methacrylate) and poly(dimethylsiloxane) via RAFT and DA click chemistry. Highlights: New ABA tri-block copolymers of PFMA & PDMS were prepared via RAFT polymerization. The thin film of BCP showed nano-phase morphology studied by AFM analysis. The BCP demonstrated self-healing property via the reversible DA & rDA reaction. The self-healing polymer was hydrophobic in nature due to presence of PDMS.